Wear Reliability and Sensitivity Analysis of the Chain Plate in the Leaf Chain - Wen Sun; Tao Ren; Wei Zeng; Xiaoqing Kang (Jixie chuandong, 2021)
Chain drive has wide applications in engineering field. The wear failure of chain plate in the chain will lead to the decrease of fatigue strength and life，so it is important to analyze the wear reliability of the chain plate. Based on the Archard model，the reliability calculation model of the wear depth of the chain plate is established，the wear reliability and sensitivity analysis method of the chain plate is proposed，and the case analysis of the wear reliability of the chain plate in the leaf chain motion mechanism is carried out. The results show that distributed parameters of different random variables have different influence on failure probability. The sliding distance has the greatest influence on the failure probability of the chain plate. The wear allowance，material hardness and contact stress have great influence on the failure probability of the chain plate，and the wear coefficient has relatively little effect on the failure probability of the chain plate. The mean of the wear allowance and material hardness have negative effect on the failure probability of the chain plate，but other distributed parameters have positive effect on the failure probability of the chain plate.